Historical vs. present populations of the sedge Carex repens: a comparison on the basis of molecular data - Lembicz, Marlena; Rogowski, Artur; Jarmolowski, Artur; Bogdanowicz, Agnieszka M.; Zukowski, Waldemar (Phytotaxa, 2013)
Polish historical and present populations of Carex repens (= C. posnaniensis) were compared with southern European populations of this plant on the basis of their nuclear ITS and chloroplast IGS DNA sequences. It follows from the analysis of the available data that (1) there are no differences in ITS1 and ITS2 sequences between the present populations occurring nearby the Jajtawy population (Poland), where in 1896 Spribille described C. posnaniensis, (2) the taxonomic distance between all the populations is relatively small (the greatest was reported between the populations from Poland and Italy), (3) the similarity between the populations decreases with an increasing geographical distance between them. Two populations from Italy exhibit the highest taxonomic distance from the Polish ones. We attribute this finding to the difference in age between these populations, as the Polish populations are much younger relative to the Italian ones and they could have appeared only after the Baltic glaciation ice sheet had receded.